Factors Related to the Unsafe Act in Office Construction Project Workers at PT. X North Jakarta, Indonesia - Simopiaref, Yacoba Jennyver (Archives of The Medicine and Case Reports, 2024)
Unsafe act is a worker's failure to follow correct work procedures, giving rise to the potential for work accidents. Human factors with unsafe act are the cause of 85% of work accidents. This research aims to determine factors related to unsafe act, namely K3 knowledge, K3 supervision, K3 training, and fatigue in office construction project workers by PT. X in North Jakarta. This type of research is quantitative with a cross sectional study design. The research sample used a total sampling of 72 workers. Research variables were analyzed using the Chi-square test. The highest proportion of respondents were workers who behaved safely (53%), had good K3 knowledge (66%), good K3 supervision (65%), had attended K3 training (54%), and experienced severe fatigue (54%). Bivariate results show a relationship between K3 knowledge (p-value = 0.020), K3 training (p-value = 0.001), and fatigue (p-value = 0.004) with unsafe act. There is no relationship between K3 supervision (p-value = 0.731) and unsafe act. In conclusion, K3 knowledge, K3 training, and fatigue are related to unsafe act in workers.